A Critical Period for the Development of Schizophrenia-Like Pathology by Aberrant Postnatal Neurogenesis - Sheu, Joen-Rong; Hsieh, Cheng-Ying; Jayakumar, Thanasekaran; Tseng, Mei-Fang; Lee, Hsing-Ni; Huang, Shin-Wei; Manubolu, Manjunath; Yang, Chih-Hao (Frontiers in Neuroscience, 2019)
Schizophrenia is a complex and serious mental disorder, and patients with schizophrenia are characterized by psychological hallucinations, deregulated emotionality, and cognitive impairment. Evidence indicated that postnatal neurogenesis in the hippocampus is profoundly impaired in schizophrenic individuals but the role of such dysregulated neurodevelopmental processing in the pathophysiological progress of schizophrenia has not been well investigated. Here in this study, by using the rodent model of schizophrenia through maternal immune activation of poly (I:C) injection, we aimed to examine whether the postnatal neurogenesis might be involved in the development of schizophrenia-like pathology. Through the comprehensive behavioral analyses of multiple core symptoms of schizophrenia at different developmental stages (6-, 9-, and 12-weeks after birth) of the affected offspring, we found a delayed onset of schizophrenia-like behaviors in poly (I:C) animals through the development. Meanwhile, there is an age-dependent alteration of postnatal neurogenesis in the poly (I:C) animals along different development stages by which the aberrant dendritic elaboration functionally correlated with the schizophrenia-like symptoms in 9-week-old of age for the animals. Interestingly, increase in the neurogenesis during a critical period of neurodevelopment exacerbates the schizophrenia-like pathology. Conversely, temporal suppression of aberrant postnatal neurogenesis during the same period of neurodevelopment ameliorates the occurrence of schizophrenia-like symptoms. Together, these findings strongly suggested the aberrant dendritic growth of postnatal neurogenesis during the critical time window of development is essential for controlling the pathophysiological progression of schizophrenia-like symptoms. And pharmacological treatments that adjust these abnormalities may provide potential therapeutic benefits toward patients with schizophrenia in clinic.